Functional consequences of novel connexin 26 mutations associated with hereditary hearing loss - Mani, Ram Shankar (Nature Publishing Group, 2009)
In a study of 530 individuals with non-syndromic, sensorineural hearing loss, we identified 18 mutations at connexin 26 (Cx26), four of which are novel (−23G>T, I33T, 377_383dupTCCGCAT, W172R) and the remaining 14 (ivs1+1G>A, M1V, 35delG, W24X, I35S, V37I, R75W, W77X, 312del14, E120del, Q124X, Y136X, R143W, R184P) being mutations previously described. To gain insight into functional consequences of these mutations, cellular localization of the mutant proteins and their ability to permit lucifer yellow transfer between cells was studied in seven of them (W24X, I33T, I35S, R75W, E120del, W172R and R184P). I35S and R184P showed impaired trafficking of the protein to the plasma membrane. I33T, R75W, E120del and W172R showed predominantly membrane localization but did not form functional gap junction channels. Surprisingly, W24X, a protein-truncating mutation, apparently permits formation of a full-length protein, perhaps due to a stop codon read-through mechanism. These results provide further evidence that Cx26 mutations affect gap junction activity by mis-regulation at multiple levels.